Sustainable Protein Sources: Functional Analysis of Tenebrio molitor Hydrolysates and Attitudes of Consumers in Poland and Spain Toward Insect-Based Foods - Marcelina Maciejewska; Anna Dąbrowska; Marina Cano-Lamadrid (Foods)
This study explores the potential of Tenebrio molitor protein hydrolysates as functional food ingredients, evaluating their bioactivity and consumer acceptance of the incorporation of edible insects into food across Poland and Spain. By aligning technical advancements with consumer preferences, this research bridges the gap between laboratory innovation and market feasibility, contributing to the development of sustainable functional foods. The study optimized the process of enzyme hydrolysis using serine protease from Cucurbita ficifolia, thereby enhancing DPPH scavenging capacity increased from 3.15 ± 0.53 to 8.17 ± 0.62 µM Trolox/mL and ABTS decolorization capacity increased from 4.29 ± 0.01 to 10.29 ± 0.01 µM Trolox/mL after 5 h of hydrolysis. Consumer surveys incorporating the Food Neophobia, Insect Phobia, and Entomophagy Scales revealed demographic and cultural influences on entomophagy acceptance. Among respondents, 27.1% in Poland and 25.7% in Spain had previously consumed insect-based products, while Polish participants showed a higher willingness to adopt insect-enriched foods. The study confirmed that hydrolysis enhances the antioxidant activity of T. molitor protein hydrolysates and that demographic and cultural factors significantly influence consumer acceptance of insect-based foods.